2016
DOI: 10.11648/j.ajep.20160505.14
|View full text |Cite
|
Sign up to set email alerts
|

Production and Fuel Properties of Biodiesel from Gingerbread Plum (<i>Parinari macrophylla</i>) Seed Oil Using MgO/Al<sub>2</sub>O<sub>3</sub> Catalyst

Abstract: Abstract:Increase in environmental pollution due fossil fuel exhaust emissions coupled with petroleum fuel depletion leads to search for the alternative green sources of energy. In views of this, methanolysis of gingerbread plum (Parinari macrophylla) seed oil had been carried out using 5wt.% MgO/Al 2 O 3 catalyst to produce biodiesel and assess its fuel quality as a source of green energy. The results produced a biodiesel with 97% yields, 0.60g/cm 3 density, 0.42% water and sediment content, 0.45mg/KOH acid v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…Water and sediment, presented in table 1, was found (0.08%) to be higher than the recommended values for biodiesel by ASTM (2007). The result agreed with the findings of who studied the production and properties of diesel produced from Ginger breed Plum seed oil [11]. Water interacts with the methyl ester biodiesel to form free fatty acids which results in microbial growth in the storage tank.…”
Section: Physicochemical Parameterssupporting
confidence: 90%
See 2 more Smart Citations
“…Water and sediment, presented in table 1, was found (0.08%) to be higher than the recommended values for biodiesel by ASTM (2007). The result agreed with the findings of who studied the production and properties of diesel produced from Ginger breed Plum seed oil [11]. Water interacts with the methyl ester biodiesel to form free fatty acids which results in microbial growth in the storage tank.…”
Section: Physicochemical Parameterssupporting
confidence: 90%
“…Table 1 also showed that the specific gravity (0.85) was within the accepted levels (0.90) recommended by ASTM6571 (2007) for biodiesel which agrees with the findings of Hassan LG, et al (2007) [15]. It further validated the saponification value of 16.83 mg KOH/g which suggested high molecular weight and may be responsible for the high density as reported by Mukhtar M, et al (2016) [11].…”
Section: Physicochemical Parameterssupporting
confidence: 86%
See 1 more Smart Citation
“…It is fuel quality parameter that is related to the ignition delay time and combustion quality of a fuel, it measures the readiness of a diesel fuel to auto ignite when injected into the diesel engine [29]. A fuel with high cetane number indicates good ignition quality, the higher the cetane number the shorter the ignition delay and the higher the propensity of the fuel to ignite [30].…”
Section: Discussionmentioning
confidence: 99%
“…Quality characteristics and antioxidant properties of gingerbread plum (Neocarya macrophylla) seed oils was also reported [7]. To provide another source of greener energy MgO/Al 2 O 3 catalyst was used to produce biodiesel from gingerbread plum (Parinari macrophylla) seed oil [8]. This research work is aimed at fatty acid analysis of Neocarya macrophylla seed oil by qualitative method and characterization by Gas Chromatography-Mass Spectrometry (GC-MS) Analysis and Fourier Transform Infra-Red (FT-IR).…”
Section: Introductionmentioning
confidence: 99%